Integration of national minorities in Georgia is an important condition for State and democratic development - Nino Dekanoidze (Zien Journals, 2023)
The multinational Georgian State, populated by ethnic minorities, has been working for many years to identify problems existing in different parts of the country in order to develop an effective strategy and a long-term plan for the civic integration of minorities in the process of building a fullfledged democracy. One of the obstacles to the civic integration of ethnic minorities is ignorance of the State language, the language barrier creates a lack of communication in society, and this problem hinders civic integration in many directions. The problem of awareness determines the passive role of ethnic minorities in public life, which leads to their isolation from the rest The unity of society creates a difficult situation for them. The problem is the lack of access of ethnic minorities to public services, informing the public about legislative innovations, etc., which may also be related to problems in the State language and the education system. The language barrier leads to the closeness of ethnic minorities in relation to the rest of society and less communication with the state, which increases the risks of general dissatisfaction with ethnic minorities, a high level of general dissatisfaction can also lead to the risks of small conflicts, which, depending on the general situation, can disrupt peace in the country. state and Stability creates a problem. Proceeding from the above, the elimination of the problem of ignorance of the state language, informing the society populated by ethnic minorities, and a high level of communication is one of the main priorities of the state, the search for effective solutions to which should be a permanent priority of the state.
Keywords: National minorities; integration of ethnic minorities; building democracy